CD9 Tetraspanin: A New Pathway for the Regulation of Inflammation? - Brosseau, Carole; Colas, Luc; Magnan, Antoine; Brouard, Sophie (Frontiers in Immunology, 2018)
CD9 belongs to the tetraspanin superfamily. Depending on the cell type and associated molecules, CD9 has a wide variety of biological activities such as cell adhesion, motility, metastasis, growth, signal transduction, differentiation and sperm–egg fusion. This review focuses on CD9 expression by hematopoietic cells and its role in modulating cellular processes involved in the regulation of inflammation. CD9 is functionally very important in many diseases and is involved either in the regulation or in the mediation of the disease. The role of CD9 in various diseases, such as viral and bacterial infections, cancer and chronic lung allograft dysfunction, is discussed. This review focuses also on its interest as a biomarker in diseases. Indeed CD9 is primarily known as a specific exosome marker however, its expression is now recognized as an anti-inflammatory marker of monocytes and macrophages. It was also described as a marker of murine IL-10-competent Breg cells and IL-10-secreting CD9+ B cells were associated with better allograft outcome in lung transplant patients, and identified as a new predictive biomarker of long-term survival. In the field of cancer, CD9 was both identified as a favorable prognostic marker or as a predictor of metastatic potential depending on cancer types. Finally, this review discusses strategies to target CD9 as a therapeutic tool. Because CD9 can have opposite effects depending on the situation, the environment and the pathology, modulating CD9 expression or blocking its effects seem to be a new promising therapeutic strategy.